Dual mobility total hip arthroplasty in complex cases - Tigani, Domenico; Castiello, Emanuela; Moghnie, Alessandro; Comitini, Saverio; Ganci, Marco; Consoli, Alberto; Berti, Matteo; Amendola, Luca (Lo Scalpello - Journal, 2021)
Since their launch on the market in the late 1970s, Dual Mobility Cups (DMCs) have shown encouraging results both in terms of stability and of restoration of wide hip joint amplitude. Therefore, the use of DMCs is mainly indicated for patients at risk of dislocation, such as those with neuro-muscular diseases, femoral neck fractures, or complex situations like failed hip osteosynthesis, as well as being indicated in the setting of revisions. The objective of this review is to provide indications and recommendations for orthopedic surgeons using DMCs in complex primary and revision settings. An overview of the tech- nical and theoretical requirements necessary to achieve a successful DMC implantation is presented. According to the literature, indications have been expanded thanks to the constant improvement and development of materials and implants. Nowadays, the use of DMCs is no longer limited to revision surgery alone; on the contrary, increasingly complex cases may be approached. Long-term studies are needed before any formal conclusions can be drawn an before the promising results that have been obtained in difficult cases are consolidated.